Management of Typical and Atypical Hangman's Fractures. (May 2016) - Al-Mahfoudh, Rafid; Beagrie, Christopher; Woolley, Ele; Zakaria, Rasheed; Radon, Mark; Clark, Simon; Pillay, Robin; Wilby, Martin
Study Design: Retrospective study of a prospectively maintained database. Objective: Our aim was to retrospectively review management and outcomes of patients with low-grade hangman's fractures, specifically looking at differences in outcomes between collars and halo immobilization. We also studied fracture patterns and their treatment outcomes. Methods: Forty-one patients with hangman's fractures were identified from 105 patients with axis fractures between 2007 and 2013. Typical hangman's fractures were defined as traumatic spondylolisthesis of the axis causing a bilateral pars interarticularis fracture. Fractures involving the posterior cortex of C2 on one or both sides or an asymmetrical pattern were defined as atypical. Results: There were 41 patients with a mean age of 59 years, with 13 (31.7%) typical and 28 (68.2%) atypical fractures. There were 22 (53.6%) type 1 fractures, 7 (41.4%) type 2 fractures, and 2 (4.9%) type 2a fractures in this series. Cervical collars were used to manage 11 patients (27% of all patients with hangman's fractures) and halo orthosis was used in 27 (65.8%). Three (7.3%) patients underwent surgical fixation of the fracture. Bony union was achieved in all patients on radiologic follow-up. Permanent neurologic deficit occurred in one patient due to associated injuries. Neck pain and stiffness were reported more commonly in the atypical group, but this finding was not statistically significant. Conclusions: The majority of hangman type fractures can be treated nonoperatively. We found no difference in outcomes between a rigid collar or halo immobilization for treatment of low-grade fractures. Radiologic follow-up is essential to identify cases of nonunion.